2014
DOI: 10.1111/ijfs.12730
|View full text |Cite
|
Sign up to set email alerts
|

Application of cold oxygen plasma for the reduction of Cladosporium cladosporioides and Penicillium citrinum on the surface of dried filefish (Stephanolepis cirrhifer) fillets

Abstract: This study was conducted to investigate the effects of cold oxygen plasma (COP) on the reductions of Penicillium citrinum and Cladosporium cladosporioides on the surface of dried filefish fillets (Stephanolepis cirrhifer). The counts were significantly (P < 0.05) reduced with the increase in the treatment time (3-20 min) of COP on the fillets. However, no significant (P > 0.05) differences were observed in the counts between 3 and 5 min of COP. The average decrease in the counts of C. cladosporioides and P. ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Microbial inactivation has commonly been modeled using a first-order kinetics process ( Whiting et al., 1996 ; Pankaj et al., 2013 ) fitted for comparison with the Weibull model. Moreover, many researchers have revealed that the Weibull model might have a better fit than first-order models for kinetic viability of bacteria and viruses, such as mixed-culture biofilms of S. Typhimurium ( Jahid et al., 2015 ), reduction of Cladosporium cladosporioides and Penicillium citrinum ( Park and Ha, 2015 ), and survival of norovirus ( Kim et al., 2014 ) and the hepatitis A virus ( Bae et al., 2014 ). Thus, for its simplicity and flexibility, the Weibull model is used extensively ( Chen and Hoover, 2004 ; Chen, 2007 ; Muñoz-Cuevas et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial inactivation has commonly been modeled using a first-order kinetics process ( Whiting et al., 1996 ; Pankaj et al., 2013 ) fitted for comparison with the Weibull model. Moreover, many researchers have revealed that the Weibull model might have a better fit than first-order models for kinetic viability of bacteria and viruses, such as mixed-culture biofilms of S. Typhimurium ( Jahid et al., 2015 ), reduction of Cladosporium cladosporioides and Penicillium citrinum ( Park and Ha, 2015 ), and survival of norovirus ( Kim et al., 2014 ) and the hepatitis A virus ( Bae et al., 2014 ). Thus, for its simplicity and flexibility, the Weibull model is used extensively ( Chen and Hoover, 2004 ; Chen, 2007 ; Muñoz-Cuevas et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Spores in general are highly resistant against all kinds of disinfection, which also explains the long inactivation time. On dried filefish fillets, P. citrinum was reduced by 1 log CFU/g after 10 min of cold oxygen plasma treatment ( Park and Ha, 2014 ). Penicillium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Other inexpensive methods for measurement of plasma species include the use of optical absorption spectroscopy (OAS); cf. Moiseev et al (2014), and Park, Choe, and Jo (2018).…”
Section: Plasma Chemistrymentioning
confidence: 99%